Pembuatan sistem untuk meratakan padi otomatis menggunakan remote control dan detector object - Husnuli Karim (PILLAR OF PHYSICS, 2016)
Drying rice in Indonesia still uses conventional way. This drying process usually use the traditional tool. The weakness of this tool is pushed and pulled by human. A solution to solve this problem is to make an automatic system to flat th rice by using remote control and detector object. This system is completed by detector object sensor. The objective of this research is to determine performance specification and design specification of this system. This research design is engineering research. This engineering research is the research who applied the knowledge to make a design in some tool. Electronic circuit design of system is usually described in diagram block. This diagram block consist of transmitter, receiver, microcontroller, motor driver, DC motor, PING sensor, and buzzer. The physic quantities in this research was distance and frequency. Research of this research can be devided into two part.  The specification design of system completed with remote control and PING sensor. This system made from wood that combine with tube plastic. This system has 1.3 m of lengt and 1 m of wide with 4 wheels and a thruster, the thruster power of motor can be pushed 5 kg mass of rice. PING sensor have 98.6 % of accuration and have 0.997 precission. The transmitter and receiver have frequency 25 MHz with relative accuration 92.529 % and precission 0.991. Remote control has an average range 16.99 m with precission 0.999. This system can flat the rise up to 5.93 m with relative accuration 0.9 and can flat the rice with thickness 1.15 with precission 0.95